2020
DOI: 10.1097/md.0000000000019337
|View full text |Cite|
|
Sign up to set email alerts
|

Respiratory muscle training in stroke patients with respiratory muscle weakness, dysphagia, and dysarthria – a prospective randomized trial

Abstract: Objective: To examine the efficacy of combined inspiratory and expiratory respiratory muscle training (RMT) with respect to the swallowing function, pulmonary function, functional performance, and dysarthria in patients with stroke. Design: Prospective, randomized controlled trial. Setting: Tertiary hospital. Participants: The trial included 21 subjects (12 men, 9 women) aged 35 to 80 years presenting with 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 33 publications
1
68
0
9
Order By: Relevance
“…The subgroup analysis by type of intervention showed a slightly greater effect in the pooled of the studies that performed only IMT [ES= 0.89 (95% CI: 0.19 to 1.58; I 2 = 66.3%, p = 0.018)] compared with the IMT/EMT subgroup [ES= 0.38 (95% CI: 0.06 to 0.69; I 2 = 0.0%, p = 0.650)]. The FVC was analysed in nine studies [19,23,25,27,29,32,34,36,37]. The pooled ES was 0.32 (95% CI: 0.06 to 0.58; I 2 = 0.0%, p = 0.507) ( Figure 3).…”
Section: Pulmonary Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…The subgroup analysis by type of intervention showed a slightly greater effect in the pooled of the studies that performed only IMT [ES= 0.89 (95% CI: 0.19 to 1.58; I 2 = 66.3%, p = 0.018)] compared with the IMT/EMT subgroup [ES= 0.38 (95% CI: 0.06 to 0.69; I 2 = 0.0%, p = 0.650)]. The FVC was analysed in nine studies [19,23,25,27,29,32,34,36,37]. The pooled ES was 0.32 (95% CI: 0.06 to 0.58; I 2 = 0.0%, p = 0.507) ( Figure 3).…”
Section: Pulmonary Functionmentioning
confidence: 99%
“…When the studies were removed one by one, the pooled ES analysis showed a loss of statistical significance when the study of NJ Jung et al [26] was removed. Dyspnea was evaluated in five studies [19,21,29,33,37]; due to the limited number of studies, the subgroup analysis by type of RMT exercise was not performed. The pooled ES of RMT interventions on dyspnea was 0.47 (95% CI: −0.30 to 1.23; I 2 = 77%, p = 0.002) (Figure 8), showing a positive trend of improvement which was not statistically significant.…”
Section: Functional Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Improving rehabilitation training at this stage can help a lot to restore swallowing function as much as possible 24 . Previous study 25 has pointed out that it is rather difficult to evaluate the recovery of neurological function after stroke, and rehabilitation training at the initial stage can restore and alleviate the symptoms of dysphagia in most patients. The results of this present study have indicated that capsaicin combined with ice stimulation is beneficial to the recovery of swallowing function in patients with dysphagia after stroke, which is an easy and convenient intervention to improve the prognosis of patients with dysphagia.…”
Section: Discussionmentioning
confidence: 99%